2013
DOI: 10.3319/tao.2012.10.23.01(a)
|View full text |Cite
|
Sign up to set email alerts
|

Characteristics of Summertime Circulation Patterns for Southern Taiwan’s Monsoon Rainfall from July to September

Abstract: This study documents the circulation features associated with summer monsoon rainfall over southern Taiwan from July through September over the period 1974 -2001. Four types of monsoon systems, Monsoon I, I-TC, II and II-TC, are identified based on the daily rainfall data of 4 observational stations over southern Taiwan and the daily wind direction data of Lanyu. The total rainfall amount of Monsoon I and I-TC is much greater than that for Monsoon II and II-TC because the former two have more moisture. Monsoon… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
4
0

Year Published

2014
2014
2019
2019

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 15 publications
1
4
0
Order By: Relevance
“…The northerly wind associated with Wukong's outer circulation over southeastern China coast converged with westerly wind over southern Taiwan Strait and northeastern SCS. The flow pattern is similar to Monsoon I-TC type proposed by Ko & Tzeng (2013). The westerly wind was about 3 ms -1 , which gave a low F w~0 .15.…”
Section: Case B (18-19 August 2006)supporting
confidence: 48%
See 1 more Smart Citation
“…The northerly wind associated with Wukong's outer circulation over southeastern China coast converged with westerly wind over southern Taiwan Strait and northeastern SCS. The flow pattern is similar to Monsoon I-TC type proposed by Ko & Tzeng (2013). The westerly wind was about 3 ms -1 , which gave a low F w~0 .15.…”
Section: Case B (18-19 August 2006)supporting
confidence: 48%
“…Meanwhile, the western Pacific high pressure extended to The Philippines resulting in southwesterly flow over northern SCS, Taiwan Strait, and Taiwan. The flow pattern is similar to Monsoon I type proposed by Ko & Tzeng (2013). The low-level prevailing southwesterly wind speed was about 8.8 m s -1 and the F w is about 0.3 (h~2500 m and N w~0 .01 s -1…”
Section: Case a (9-10 July 2008)mentioning
confidence: 55%
“…To isolate the intraseasonal signals, the Butterworth bandpassed filter (Kaylor 1977), which was employed by Hsu and Weng (2001), Ko andHsu (2006, 2009), and Ko et al (2012), was applied in this study to extract the 30-80-day (intraseasonal) fluctuations.…”
Section: Data and Analysis Proceduresmentioning
confidence: 99%
“…Ko and Hsu (2009) examined the effect of ISO modulation on submonthly wave patterns (Ko and Hsu 2006) propagating north-northwestward from the northeast of Papua New Guinea to the oceanic area between Taiwan and Japan. They reported that when the ISO cyclonic circulation propagated northwestward (Wang and Rui 1990;Hsu and Weng 2001;Tsou et al 2005), the submonthly wave pattern during the ISO westerly phase was better organized in the cyclonic and moistureconverging environment of a strong eastward-extending monsoon trough.…”
Section: Introductionmentioning
confidence: 99%
“…26 also indicated that the changes of the SSTA in the tropical Pacific and the Indian Ocean impact the changes of the WNPSH. Because the changes in the EASM circulation, moisture transport and WNPSH are the most important factors that affect the CAR formation in Taiwan 10,27,28 , we then hypothesize based on these documented studies that (1) there might be a close relationship between the interannual variation of CAR activity in Taiwan and SSTA over the tropical Pacific regions, and (2) this relationship might have changed after the 1990s. These two hypotheses will be examined herein.…”
Section: Introductionmentioning
confidence: 99%